Composition of the Intestinal Microbiota Determines the Outcome of Virus-Triggered Colitis in Mice - Bolsega, Silvia; Basic, Marijana; Smoczek, Anna; Buettner, Manuela; Eberl, Claudia; Ahrens, Daniel; Odum, Kodwo Appoh; Stecher, Bärbel; Bleich, Andre (Frontiers in Immunology, 2019)
The intestinal microbiota is a complex ecosystem implicated in host health and disease. Inflammatory bowel disease (IBD) is a multifactorial chronic disorder of the gastrointestinal mucosa. Even though the exact mechanisms are still unknown, the intestinal microbiota is crucial in IBD development. We previously showed that murine norovirus (MNV) induces colitis in the Il10-deficient (Il10-/-) mouse model of IBD in a microbiota-dependent manner. Thus, in this study we analyzed whether distinct minimal bacterial consortia influence the outcome of MNV-triggered colitis in Il10-/- mice. Gnotobiotic Il10-/- mice associated with Oligo-Mouse-Microbiota 12 (OMM12) or Altered Schaedler Flora (ASF) developed little to no inflammatory lesions in the colon and cecum. MNV infection exacerbated colitis severity only in ASF-colonized mice, but not in those associated with OMM12. Four weeks after MNV infection, inflammatory lesions in ASF-colonized Il10-/- mice were characterized by epithelial hyperplasia, infiltration of inflammatory cells and increased barrier permeability. Co-colonization of ASF-colonized Il10-/- mice with segmented filamentous bacteria (SFB) abolished MNV-induced colitis, whereas histopathological scores in SFB-OMM12-co-colonized mice stayed unchanged. Moreover, SFB only colonized mice associated with ASF. The SFB-mediated protective effects in ASF-colonized mice involved enhanced activation of intestinal barrier defense mechanisms and mucosal immune responses in the chronic and acute phase of MNV infection. SFB colonization strengthened intestinal barrier function by increasing expression of tight junction proteins, antimicrobial peptides and mucus. Furthermore, SFB colonization enhanced the expression of pro-inflammatory cytokines such as Tnf, Il1, and Il12a, as well as the expression of the regulatory cytokine Tgf. Altogether, our results showed that MNV-triggered colitis depends on the microbial context.